2023
DOI: 10.1155/2023/6320490
|View full text |Cite
|
Sign up to set email alerts
|

Combined Performance of Polyethylene Terephthalate Waste Plastic Polymer and Crumb Rubber in Modifying Properties of Hot Mix Asphalt

Abstract: Nowadays, the use of recycled waste materials in road pavement is regarded not only as a positive option in terms of sustainability but also as an appealing option in terms of providing improved service performance. The current study aimed at evaluating the performance of crumb rubber and polyethylene terephthalate plastic polymer in asphalt mixture in modifying the mechanical properties of asphalt pavement. Experimental tests were carried out both for asphalt binder and asphalt mixture. Different proportions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Although a mixing time of 1 h is generally suggested for modifying bitumen with plastics, this study employed a shorter mixing time of 30 min for preparing PMB. This is because multiple studies have concluded that the optimum mixing time for PET-modified bitumen is 30 min [54,55].…”
Section: Preparation Of Plastic-modified Bitumenmentioning
confidence: 99%
See 3 more Smart Citations
“…Although a mixing time of 1 h is generally suggested for modifying bitumen with plastics, this study employed a shorter mixing time of 30 min for preparing PMB. This is because multiple studies have concluded that the optimum mixing time for PET-modified bitumen is 30 min [54,55].…”
Section: Preparation Of Plastic-modified Bitumenmentioning
confidence: 99%
“…However, a higher percentage of air voids is undesirable as it creates passageways for water intrusion, thus increasing the moisture susceptibility of the asphalt mixture and facilitating the rapid deterioration of pavements. Multiple studies have concluded that the design air void level in a laboratory-compacted sample of HMA ought to be 4 percent for assessing the optimum moisture resistance of asphalt mixtures [55,57].…”
Section: Marshall MIX Design-obc Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, these recycled materials have the potential to enhance the performance of road surfaces, resulting in improved durability and cost-effectiveness. Overall, the utilization of recycled waste materials in road pavement is seen as a promising and environmentally friendly solution [5]. The utilization of CR derived from discarded tires to enhance the mechanical properties of bituminous mixtures has become highly significant in the field of road engineering.…”
Section: Introductionmentioning
confidence: 99%